Refugees in our own land : chronicles from a Palestinian refugee camp in Bethlehem - Hamzeh, Muna, 1959- (London ; Sterling, Va. : Pluto Press, 2001)
This book is an eye-witness account of what it is like to live in Palestine as a refugee in your own homeland. Born in Jerusalem, Muna Hamzeh is a journalist who has been writing about Palestinian affairs since 1985. She first worked as a journalist in Washington DC, but moved back to Palestine in 1989 to cover the first Palestine Intifada - the war of stones. She then settled in Dheisheh, near Bethlehem, - one of 59 Palestinian refugee camps that are considered the oldest refugee camps in the world. Immediately accessible and fully up-to-date, the first part of the book consists of a diary which Hamzeh wrote between October 4th and December 4th 2000, telling the story of the second Intifada. Facing the tanks and armed guards of one of the best equipped armies in the world, the Palestinians have nothing. They fight back with stones. The anguish and terror that Muna and her friends face on a daily basis is tangible. Who will be the next to die? Whose house will be the next to burn down? This deeply moving personal account brings to life the harsh realities of the Palestinian struggle. The second part of the book provides the background to these current events. It describes what life has been like for Dheisheh's refugees since 1990, and explains why the second Intifada was a natural development of the Oslo peace accord. -- Publisher description.
Part I. 1. Ordinary days in Dheisheh (2000) ---- Part II. 2. Farewell Washington (1988) --- 3. Welcome to Dheisheh (1990) --- 4. Urging on the scuds (1991) --- 5. Diary of a blockade (1993) --- 6. Fatima (1994) --- 7. Dheisheh will never fall again (1995) --- 8. Where is peace? (1996) --- 9. When time stood still (1996) --- 10. The French connection (1997) --- 11. The glory of the Intifada (1997) --- 12. Where do we belong? (1997) --- 13. Remembering our dead (1997) --- 14. Where did Santa go? (1998) --- 15. Male vs. female honor (1998) --- 16. Celebrating independence (1998) --- 17. From Dheisheh to Jerusalem (1998) --- 18. Making it in a man's world (1998) --- 19. Diving with a splash (1998) --- 20. Life's four seasons (1998) --- 21. Checkpoint Jerusalem (1999) --- 22. The Pope in our midst (2000).
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Hamzeh, Muna, -- 1959- -- Diaries; Hamzeh, Muna, -- 1959-; Duhayshah (Refugee camp); Al-Aqsa Intifada, 2000-2005 -- Personal narratives, Palestinian; Palestinian American journalists -- Diaries; Refugees, Palestinian Arab -- West Bank -- Duhayshah (Refugee camp) -- Social conditions; HISTORY -- General; POLITICAL SCIENCE -- Human Rights; Palestinian American journalists; Refugees, Palestinian Arab -- Social conditions; Vluchtelingenkampen; Palestijnen; Intifadah; Since 2000; Personal narratives; Diaries; Personal narratives -- Palestinian; Dagboeken (vorm); Personal narratives; Récits personnels